Rheological and mechanical properties of acellular and cellladen methacrylated gellan gum hydrogels - Silva-Correia, Joana (2013)
Tissue engineered hydrogels hold great potential as nucleus pulposus substitutes (NP), as they promote intervertebral disc (IVD) regeneration and re-establish its original function. But, the key to their success in future clinical applications greatly depends on its ability to replicate the native 3D micro-environment and circumvent their limitation in terms of mechanical performance. In the present study, we investigated the rheological/mechanical properties of both ionic- (iGG-MA) and photo-crosslinked methacrylated gellan gum (phGG-MA) hydrogels. Steady shear analysis, injectability and confined compression stress-relaxation tests were carried out. The injectability of the reactive solutions employed for the preparation of iGG-MA and phGG-MA hydrogels was firstly studied, then the zero-strain compressive modulus and permeability of the acellular hydrogels were evaluated.In addition, human intervertebral disc (hIVD) cells encapsulated in both iGG-MA and phGG-MA hydrogels were cultured in vitro, and its mechanical properties also investigated under dynamic mechanical analysis at 37ºC and pH 7.4. After 21 d of culturing, hIVD cells were alive (Calcein AM) and the E’ of ionic-crosslinked hydrogels and photo-crosslinked was higher than that observed for acellular hydrogels. Our study suggests that methacrylated gellan gum hydrogels present promising mechanical and biological performance as hIVD cells were producing extracellular matrix.